Residential radon exposure and cancer - Akhila Reddy; Camila Conde; Christopher Peterson; Kenneth M Nugent (Frontiers Media S.A., 2022)
Radon is an established human lung carcinogen naturally released as an odorless, colorless gas from soil and rocks. It is a major environmental source of ionizing radiation and can cause oxidative damage to DNA, increasing the risk of cancer. Although the association between radon and lung cancer is well established, the association between radon and other cancers is not. Based on reported studies, there is no consistent evidence indicating an association between radon and non-lung cancers, but limited literature, heterogenous study design, and confounding variables preclude definitive conclusions.  More research is needed to evaluate the association between residential radon and non-lung cancers, particularly with regard to skin cancer, CNS cancer, and stomach cancer, in which existing literature suggests potential associations with residential radon may exist. However, the literature largely demonstrates that lung cancer is the primary concern associated with residential radon exposure and that non-lung cancers are secondary concerns. These results should be considered in residential radon mitigation efforts.